PENGEMBANGAN MODUL PEMBELAJARAN TERPADU UNTUK MAHASISWA PG-PAUD UNIVERSITAS MUSAMUS - Rafi’y, Muh (Penerbit Widina, Widina Media Utama, 2022)
This study aims to develop a valid and practical integrated learning module that can be used in the learning process in the S1 Early Childhood Education Teacher Education (PG-PAUD) study program at Musamus Merauke University. The research method used is the ADDIE type Research and Development (RD) model which consists of Analysis, Design, Development, Implementation and Evaluation. Data collection is carried out through expert tests including media experts and material experts. The development of integrated learning modules is said to be valid which is proven through the results of assessments by material experts and media experts. The integrated learning modules developed are feasible in terms of presentation and are in accordance with the characteristics of the targets referring to the existing RPS. It can be concluded that the integrated learning modules developed are suitable for use in the learning process at PG- PAUD Universitas Musamus Merauke.ABSTRAKPenelitian ini bertujuan untuk mengembangkan modul pembelajaran terpadu yang valid dan praktis yang dapat digunakan dalam proses pembelajaran di program studi S1 Pendidikan Guru Pendidikan Anak Usia Dini (PG-PAUD) Universitas Musamus Merauke. Metode penelitian yang digunakan adalah model Research and Development (RD) tipe ADDIE yang terdiri atas Analysis, Design, Development, Implementation dan Evaluation. Pengumpulan data dilakukan melalui uji ahli meliputi ahli media dan ahli materi. Pengembangan modul pembelajaran terpadu dikatakan valid yang dibuktikan melalui hasil penilaian oleh ahli materi dan ahli media. Modul pembelajaran terpadu yang dikembangkan sudah layak dari segi penyajian dan telah sesuai dengan karakteristik sasaran yang mengacu pada RPS yang ada. Dapat disimpulkan bahwa modul pembelajaran terpadu yang dikembangkan sudah layak digunakan dalam proses pembelajaran di PG-PAUD Universitas Musamus Merauke.